Produksi Game Edukasi Interaktif Berbasis Web “OCEAN BUDDY" sebagai Media Pendukung dalam Transmedia Animasi “Luka Lama Lautan” - Iqbal Alfaturochim; Nurmaya Prahatmaja; Andri Yanto (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2026)
Educational media play an important role in delivering learning messages; however, they are still commonly presented in a one-way and less interactive manner, causing elementary school students to become passive recipients of information. One alternative to increase learning engagement is interactive educational games, which enable users to receive information, complete learning activities, and directly evaluate their understanding. This final project aims to describe the pre-production, production, and post-production processes of the web-based interactive educational game OCEAN BUDDY as a supporting medium for the transmedia animation Luka Lama Lautan. The creation process consisted of three stages. The pre-production stage included idea development, theme research, audience identification, content preparation, and the design of the game flow and assets. The production stage involved developing visual and audio assets, the user interface, and game mechanics using Construct 2. The post-production stage included testing with fourth- and fifth-grade elementary school students, evaluation, revision, and publication through the itch.io platform. The final product is an HTML5-based educational game featuring three sections Learn, Waste Sorting, and Quiz equipped with a scoring system and time limits. Careful planning, development, testing, and revision resulted in an interactive educational medium that strengthens the animation's core message while enhancing children's understanding of the dangers of plastic waste in a more active and enjoyable way.